(untitled) (British Journal of Global Ecology and Sustainable Development, 2026)
The article investigates changes in the hematological parameters of blood in cattle affected by babesiosis in the upper regions of the Zarafshan Valley. The study was conducted on three groups of animals artificially infected with Piroplasma bigeminum strains isolated from the Bulungur, Toyloq, and Jomboy districts. It was found that during the course of the disease, the number of erythrocytes and hemoglobin decreased by 3–4 times, the hematocrit level declined, and microcytic and hypochromic anemia, leukopenia, and thrombocytopenia developed. The obtained data indicate the leading role of hemolysis and suppression of hematopoiesis in the pathogenesis of babesiosis and confirm the high diagnostic value of hematological studies for early detection and assessment of disease severity.